2009
DOI: 10.1007/s11356-009-0142-4
|View full text |Cite
|
Sign up to set email alerts
|

The variability of processes involved in transgene dispersal—case studies from Brassica and related genera

Abstract: More and more transgenic varieties are being grown worldwide harbouring genes that might potentially affect the environment (e.g. drought tolerance, salt tolerance, disease tolerance, pharmaceutical genes). This calls for a thorough risk assessment. However, in Brassica, the limited and uncertain knowledge on gene flow is an obstacle to this. Modelling of gene flow should be optimised, and modelling outputs verified in targeted field studies and at the landscape level. Last but not least, it is important to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 39 publications
0
34
0
Order By: Relevance
“…Several oilseed rape wild relative hybrids have been reported in the scientific literature, but under field conditions transgene introgression has only been confirmed only for the progeny of oilseed rape Brassica rapa hybrids (Hansen et al, 2001(Hansen et al, , 2003Warwick et al, 2003Warwick et al, , 2008Norris et al, 2004;Jørgensen, 2007). Due to ecological and genetic barriers, not all relatives of oilseed rape share the same potential for hybridisation and transgene introgression (Jenczewski et al, 2003;Chèvre et al, 2004;FitzJohn et al, 2007;Wilkinson and Ford, 2007;Devos et al, 2009;Jørgensen et al, 2009). As no or only very low numbers of viable and fertile hybrids are obtained between oilseed rape and most of its wild relatives under ideal experimental conditions (e.g., through the use of artificial pollination and embryo rescue techniques in laboratory conditions (see FitzJohn et al, 2007)), Wilkinson et al (2003) concluded that exposure under real conditions is likely to be negligible, and the probability of transgene introgression is extremely small in most instances, with the exception of B. rapa in areas where it occurs close to oilseed rape.…”
Section: It Concluded That: "In the Very Unlikely Event That Such A Hmentioning
confidence: 99%
“…Several oilseed rape wild relative hybrids have been reported in the scientific literature, but under field conditions transgene introgression has only been confirmed only for the progeny of oilseed rape Brassica rapa hybrids (Hansen et al, 2001(Hansen et al, , 2003Warwick et al, 2003Warwick et al, , 2008Norris et al, 2004;Jørgensen, 2007). Due to ecological and genetic barriers, not all relatives of oilseed rape share the same potential for hybridisation and transgene introgression (Jenczewski et al, 2003;Chèvre et al, 2004;FitzJohn et al, 2007;Wilkinson and Ford, 2007;Devos et al, 2009;Jørgensen et al, 2009). As no or only very low numbers of viable and fertile hybrids are obtained between oilseed rape and most of its wild relatives under ideal experimental conditions (e.g., through the use of artificial pollination and embryo rescue techniques in laboratory conditions (see FitzJohn et al, 2007)), Wilkinson et al (2003) concluded that exposure under real conditions is likely to be negligible, and the probability of transgene introgression is extremely small in most instances, with the exception of B. rapa in areas where it occurs close to oilseed rape.…”
Section: It Concluded That: "In the Very Unlikely Event That Such A Hmentioning
confidence: 99%
“…Several oilseed rape × wild relative hybrids have been reported in the scientific literature, but under field conditions transgene introgression has been confirmed only for progeny of oilseed rape × Brassica rapa hybrids (Hansen et al, 2001(Hansen et al, , 2003Warwick et al, 2003Warwick et al, , 2008Norris et al, 2004;Jørgensen, 2007). Due to ecological and genetic barriers, not all relatives of oilseed rape share the same potential for hybridisation and transgene introgression (Jenczewski et al, 2003;Chèvre et al, 2004;FitzJohn et al, 2007;Wilkinson and Ford, 2007;Devos et al, 2009;Jørgensen et al, 2009). As no or only very low numbers of viable and fertile hybrids are obtained between oilseed rape and most of its wild relatives under ideal experimental conditions (e.g.…”
Section: Potential For Gene Transfer 32mentioning
confidence: 99%
“…There is no evidence to suggest that HT traits in a wild relative changes its behaviour (Scheffler and Dale, 1994;Eastham and Sweet, 2002;Chèvre et al, 2004;Warwick et al, 2003Warwick et al, , 2004Warwick et al, , 2008Jørgensen, 2007;Jørgensen et al, 2009), or the scale and nature of its interactions with associated flora and fauna (Wilkinson et al, 2003;Wilkinson and Ford, 2007). Progeny from hybrids of oilseed rape and wild relatives that bear the HT trait do not show any enhanced fitness, persistence and invasiveness, and behave as conventional counterparts, unless the herbicides for which tolerance is obtained are applied .…”
Section: Wild Relativesmentioning
confidence: 99%
“…Several oilseed rape x wild relative hybrids have been reported in the scientific literature, but under field conditions transgene introgression has only been confirmed for progeny of oilseed rape x B. rapa hybrids (Hansen et al, 2001(Hansen et al, , 2003Warwick et al, 2003Warwick et al, , 2008Norris et al, 2004;Jørgensen, 2007). Due to ecological and genetic barriers, not all relatives of oilseed rape share the same potential for hybridisation and transgene introgression (Jenczewski et al, 2003; Chèvre et al, 2004;FitzJohn et al, 2007;Wilkinson and Ford, 2007; Devos et al, 2009a;Jørgensen et al, 2009). For transgene introgression to occur, both species must occur in their respective distribution range of viable pollen.…”
mentioning
confidence: 99%